Poor sleep quality and erectile dysfunction in students from a Peruvian University: A cross-sectional study - Gutierrez-Velarde, Pierina (2023)
“Objective: We aimed to evaluate the association between sleep quality and erectile dysfunction in young university students. Methods: A cross-sectional survey was conducted in men aged 18–30 years from Universidad Ricardo Palma, Lima, Peru. The survey comprised the International Index of Erectile Function, Pittsburgh Sleep Quality Index, Berlin questionnaire, and questions related to sociodemographic data. Prevalence ratios were estimated with generalized linear models. Results: Of 381 participants, the median age was 23 years. Half of the students (50.9%) had poor sleep quality, of which 72.7% had mild erectile dysfunction and 20.6% mild to moderate dysfunction. Prevalence of erectile dysfunction was significantly higher in students with poor sleep quality than in students with good sleep quality (aPR = 6.48; 95% CI: 4.58–9.17) after adjusting for age, academic year, nutritional status, and sleep apnea. In a subsequent exploratory analysis, sleep apnea was associated with a higher prevalence of erectile dysfunction (aPR = 1.19; 95% CI: 1.01–1.39), while overweight (aPR = 0.85; 95% CI: 0.76–0.95) and obesity (aPR = 0.65; 95% CI: 0.52–0.82) were associated with a lower prevalence of this condition. Conclusion: Poor sleep quality was independently associated with erectile dysfunction in young university students. This finding suggests that male students are at risk for sexual problems due to possible academic demands and relationship issues. “